2016
DOI: 10.1016/j.str.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Dynamics Across the Bcl-2-Regulated Apoptotic Pathway Reveal Distinct Evolutionary Determinants of Specificity and Affinity

Abstract: SummaryCritical regulatory pathways are replete with instances of intra-and interfamily protein-protein interactions due to the pervasiveness of gene duplication throughout evolution. Discerning the specificity determinants within these systems has proven a challenging task. Here, we present an energetic analysis of the specificity determinants within the Bcl-2 family of proteins -key regulators of the intrinsic apoptotic pathway -via a total of ~20 ms of simulation of 60 distinct protein-protein complexes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 73 publications
1
33
1
Order By: Relevance
“…This observation was confirmed when two independent sets of randomized BH3-like sequences derived from each of five wild-type pro-apoptotic BH3 peptide was tested with Mcl-1 or Bcl-X L . Although the previous studies have identified polar interactions between specific residues responsible for high binding affinity or specificity [34][35][36] , our studies…”
Section: Computational Design Of Bh3-like Peptidesmentioning
confidence: 65%
“…This observation was confirmed when two independent sets of randomized BH3-like sequences derived from each of five wild-type pro-apoptotic BH3 peptide was tested with Mcl-1 or Bcl-X L . Although the previous studies have identified polar interactions between specific residues responsible for high binding affinity or specificity [34][35][36] , our studies…”
Section: Computational Design Of Bh3-like Peptidesmentioning
confidence: 65%
“…In RING E3s, conserved histidine and/or cysteine residues coordinate Zn 2+ to maintain the native protein structure. It has been found that preserving the template amino acid sidechain rotamer is beneficial in maintaining the stability of modeled antiapoptotic protein–BH3 peptide complexes during molecular dynamics simulations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atomistic models are, therefore, more prominent in rationalizations of specificity determinants. Calculations of electrostatic interactions with Generalized Born or Poisson-Boltzmann methods, combined with surface area, are often used in molecular mechanics, and have proven successful in identifying specificity determinants and recognition mechanisms [ 17 , 18 ]. Due to the extent of interfaces of even small protein–protein complexes, such methods are generally more successful in rationalizing protein–small molecule binding, than protein–protein binding [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preference of Bik-BH3t oB cl-x L over Mcl-1 was also proved in cellular experiments. [22] The readers may wish to refer to their study for details about the specific determinantso fe ach interaction pair. [18] Distinct binding profiles of antiapoptotic Bcl-2 proteins with BH3 peptides Herein, we have measured the binding affinitiesb etween eight BH3 peptides and five antiapoptotic Bcl-2 proteins in as ystematic manner.…”
Section: Bindingprofiles Of Hrk-bh3 and Bik-bh3mentioning
confidence: 99%
“…Previously,I vanov et al analyzed the binding energetics acrossadiverse set of complexes between antiapoptotic proteins and BH3 peptides. [22] The readers may wish to refer to their study for details about the specific determinantso fe ach interaction pair. ChemMedChem 2018ChemMedChem , 13,1763ChemMedChem -1770 www.chemmedchem.org Given the distinct binding profiles of antiapoptotic Bcl-2 proteins, af unctionala ssayn amed BH3 profiling was described in literature.…”
Section: Bindingprofiles Of Hrk-bh3 and Bik-bh3mentioning
confidence: 99%